Free Trade Agreements - Boon or Bane?": Through the Lens of PACER - Kelsey, Jane (Victoria University of Wellington Law Review, 2006)
This paper examines three dimensions of the Pacific islands’ relationship with Australia and New Zealand under the Pacific Agreement on Closer Economic Relations (PACER): first the context, where Pacific governments appear increasingly nervous about free trade negotiations, but believe they have few alternatives; second, how the complex and opaque legal framework of PACER and onerous requirements for WTO compatibility set the terms for future trade negotiations with Australia and New Zealand; and third, the inter-relationship between PACER and the Pacific Plan. It concludes that free trade negotiations risk determining the development options for the Pacific islands and leave no room for Pacific governments or people to explore genuine development alternatives.